Effects of melatonin on blood pressure, arterial stiffness and quality of life in postmenopausal women: A randomized controlled trial - Anne Kristine Amstrup; Lars Rejnmark (Elsevier, 2024)
Objectives: Studies suggest that melatonin may promote cardiovascular protection. Previous trials have primarily been performed on co-morbid patients. Little information exist on the effect in postmenopausal women with general good health. Design, participants and intervention: In a double-blinded placebo-controlled study, we randomized 41 postmenopausal women to either 10 mg melatonin per day or placebo for 3 months. Outcome measures: Outcomes of the trial was changes in blood pressure, pulse wave velocity (PWV), and quality of sleep evaluated by Pittsburgh Sleep Quality Index (PSQI). Results: Thirty-nine women completed the study. Mean age was 63 years (range 55-75 years). Over the 3 months of the trial, PWV did not differ between groups: Placebo 1.1% (IQR −2.1;9.9) vs. melatonin 0.0% (IQR-9.8;4.1), p = 0.43). The were no significant differences in blood pressure bewteen melatonin and placebo group. Both groups had a pour quality of sleep at baseline (placebo: PSQI 6.0 (IQR 3.3; 8.8) vs. melatonin PSQI 6.0 (IQR 3.0; 10.0), p = 0.94), which did not change in response to treatment. Conclusion: In healthy postmenopausal women, supplementation with 10 mg melatonin was well-tolerated, but we did not observe any significant improvements in pulse wave velocity, blood pressure or quality of sleep compared with placebo.